Can local and global knowledge be mixed? Shifting paradigms among the Bidayuhs of Sarawak - Teucher, Ulrich; Alexander Kiew, Sayok (2016)
Traditional indigenous ways of knowing have been disappearing fast, also among the Bidayuh of Western Sarawak (Malaysia), eliciting calls for the preservation of such knowledge, for example, in local cultural centers. However, what gets preserved in such centers are the material artifacts, not the traditional lived ontologies of once wholly enspirited life worlds. Our study among the Bidayuh, including surveys and interviews, points to mixed narratives of both loss and hope as Malaysia’s indigenous peoples resist assimilation, resent cultural stereotypes - and seek their part in the country’s modernization.